ESG Score and Stock Price Volatility: The Moderating Role of Dividend Policy in the Indonesian Capital Market (2023–2024) - Adri, Adri (Universitas KH. Abdul Chalim Mojokerto, 2026)
Environmental, Social, and Governance (ESG) initiatives are gaining prominence in global capital markets. Yet, prior studies show mixed results regarding how ESG performance relates to stock price volatility, especially in emerging markets such as Indonesia. Objective: This study analyzes the influence of ESG scores on stock price volatility and explores whether dividend policy moderates this relationship among firms listed on the Indonesia Stock Exchange during 2023–2024. The study applies panel data regression to Indonesian publicly listed companies over the 2023–2024 period. Stock price volatility, calculated using the Parkinson method, is used as the dependent variable. ESG scores from the Katadata ESG Index serve as the independent variable, while the dividend payout ratio functions as the moderating variable. Control variables include firm size, return on assets, and leverage. Research Results: The results indicate that ESG scores do not significantly influence stock price volatility. Meanwhile, dividend policy shows a significant positive effect, meaning that firms with higher dividend payouts experience greater, not lower, price fluctuations. The moderating role of dividend policy is also found to be insignificant. These outcomes imply that macroeconomic factors and retail investor behavior play a stronger role than ESG performance in shaping stock price volatility in Indonesia. Originality/Novelty: This research contributes evidence that the stabilizing effects of ESG initiatives and dividend policy are context dependent, influenced by market development, investor sophistication, and regulatory structures. The findings question the universal relevance of signaling theory and stakeholder theory in emerging market settings.